Peran warga negara dalam memperkuat demokrasi di Indonesia - Akmal, Ahmad Fairuzy (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that places the people as the holders of supreme sovereignty in the political decision-making process. In the Indonesian context, the success of democracy is determined not only by the existence of democratic political institutions, but also by the level of citizen participation and awareness in public life. This article aims to analyze the role of citizens in strengthening democracy in Indonesia through political participation, oversight of public policy, and strengthening public political literacy. This research uses a qualitative approach with a literature review method of various academic sources in the form of scientific journals, books, and research reports relevant to the theme of democracy and citizen participation. The results of the study indicate that active citizen involvement has a significant contribution to increasing government accountability, strengthening political legitimacy, and encouraging the creation of transparent governance. However, democracy in Indonesia still faces various challenges, such as low public political literacy, increasing political polarization, and the rampant spread of disinformation in digital media. Therefore, strengthening civic education, increasing digital literacy, and the active involvement of civil society are important strategies in strengthening the quality of democracy in Indonesia.